Zechstein Main Dolomite oil characteristics in the Southern Permian Basin: I. Polish and German sectors. (May 2018) - Słowakiewicz, Mirosław; Blumenberg, Martin; Więcław, Dariusz; Röhling, Heinz-Gerd; Scheeder, Georg; Hindenberg, Katja; Leśniak, Andrzej; Idiz, Erdem F.; Tucker, Maurice E.; Pancost, Richard D.; Kotarba, Maciej J.; Gerling, Johannes P.
Abstract: Geochemical analyses were used to classify 39 Zechstein (Late Permian, Lopingian) Main Dolomite (Ca2) crude oil samples from fields in the eastern and southern sector of the Southern Permian Basin (SPB) of Europe and to provide new insights into the origin of the oil. Geochemical data indicate that Ca2 oils were generated in the early-to-late oil window and are mostly non-waxy oils. Various biomarker and stable carbon isotopic ratios were used to identify source and depositional settings for source rocks of Ca2 oils arranged within 10 distinct oil groups. Specifically, the geochemical analyses and oil-oil correlations revealed a set of characteristic biomarkers including an even-over-odd predominance (EOP) for the C20-30 n -alkanes, C40 carotenoid occurrence (isorenieratane, chlorobactane, β -isorenieratane), bisnorhopane/hopane (BNH/H) ratios >0.1, high abundances of C35 homohopanes and elevated concentrations of C32 and C34 homohopanes, a predominance of C29 homologues among 4-desmethyl steranes in the majority of oil samples, and a high abundance of diasteranes. Stable carbon isotopes and biomarkers provided ample evidence that Ca2 oils were generated from predominantly algal-rich marly carbonate/evaporite source rocks located in the lower slope/shallow-basin and lagoonal facies of the Ca2 basin, all deposited under suboxic-anoxic (euxinic) conditions. In the case of all higher maturity oils, the source rocks could not be reliably identified but high (>2) C24 Tet/C23 values suggest a carbonate-evaporite depositional setting. Highlights: Main Dolomite oils from Germany and Poland constitute ten distinct groups. Aromatic C40 carotenoids are important correlative biomarker tools. Main Dolomite oils were generated from algal-rich marly carbonate/evaporite source rocks.